<htm>Epicharis (Epicharoides) decellii, a new neotropical species of bee (Anthophila, Centridini) from Serra da Mantiqueira region (Penedo, Itatiaia, RJ, Brazil)</htm> - Laroca, Sebastião; Nery, Letícia (Acta Biológica Paranaense, 2018)
<htm>Epicharis (Epicharoides) decellii, a new neotropical species of bee (Anthophila, Centridini) from Serra da Mantiqueira region (Penedo, Itatiaia, RJ, Brazil)</htm>